Konversi Agama di Kalangan Etnis Tionghoa: Motivasi, Adaptasi dan Konsekuensi - Rakhmat; Putri Sherina , Dessita (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2020)
This paper aims to describe the process of religious conversion conducted by five ethnic Chinese muallafs at Yayasan Haji Karim Oei Jakarta. This study also describes the state of anomie experienced by muallafs in the post-religious conversion time and the adaptation to face the anomic circumstances. A qualitative approach with case study method is the research approach used in this research. The subjects in this study consisted of five muallafs converted to Islam. Observations and interviews were used as data collection methods in this study. This study uses the concept of systemic stage model by Rambo Lewis to examine the process of religious conversion and the concept of anomie by Emile Durkheim to examine the social state of post-religious conversion. The results of this study show that the religious conversion is caused by an internal factor which is an inner crisis and also caused by external factors such as living in a social sphere dominated by the majority of Muslims, the factor of marriage, and religious lectures performed by the religious leaders. The encounter and the interaction between muallafs and religious advocates have great influence in decisions taken by muallaf. It is found that the state of anomie experienced by the five muallafs was colored by the resistance in the form of unfair treatment and discrimination against the muallafs which led them into the state of isolation from the former religious group. The five muallafs who are in the state of anomie searched for the community and it is found that muallafs had a relationship with Yayasan Haji Karim Oei Jakarta as a coaching form for Chinese muallafs. It can be concluded that the five muallafs have adapted themselves to Islam and Muslims by using conformity type of adaptation, whereas adaptation within the former religious group used the innovation type of adaptation